O "MARCO DE REFERÊNCIA DE EDUCAÇÃO ALIMENTAR E NUTRICIONAL PARA POLÍTICAS PÚBLICAS" NO BRASIL NO CONTEXTO DO ATENDIMENTO NUTRICIONAL - Irene Coutinho de Macedo; Rita de Cássia de Aquino (Universidade do Estado do Rio de Janeiro, 2018)
Nutritional care contributes to the individual being an agent of his food choices, aware of the benefits of healthy eating. It should be guided by documents such as the Marco de Referência de Educação Alimentar e Nutricional para Políticas Públicas [Food and Nutrition Education Framework for Public Policies]. This article aims to reflect on nutritional care, discussing relevant concepts such as food and nutrition education, the determinants of dietary pattern, counseling, and how the Framework can contribute with this process. The main interface points between this document and nutritional care are the need to understand the interactions and meanings that determine feeding behavior, and care should not focus only on biological aspects of nutrition. Emphasis is placed on the professional's proper posture as an educator, which favors the opening of dialogue and contributes to empowerment, promotion of self-care and generation of autonomy concerning eating behavior. Considering the complexity of food choices, instruments that collaborate with counseling and food and nutrition education can significantly contribute to democratic access to healthy food. DOI: 10.12957/demetra.2018.28663